The Strength of Gender Norms and Gender-Stereotypical Occupational Aspirations among Adolescents - Andreas Kuhn; Stefan C. Wolter (Institute of Labor Economics (IZA), 2019)
We empirically test the hypothesis that adolescents' occupational aspirations are more gender-stereotypical if they live in regions where the societal norm towards gender equality is weaker. For our analysis, we combine rich survey data describing a sample of 1,434 Swiss adolescents in 8th grade with municipal voting results dealing with gender equality and policy. We find that occupational aspirations are strongly gender-segregated and that adolescents living in municipalities with a stronger norm towards gender equality are significantly less likely to aspire for a gender-stereotypical occupation, even after controlling for individual-level controls. At the same time, gender norms have virtually no power in explaining the gender stereotypicity of individual occupational aspirations - challenging the widespread conception that societal gender norms are one of the most important determinants of occupational gender segregation. Moreover, a more detailed analysis shows that the association may mainly reflect the intergenerational transmission of occupations from parents to their children and/or regional differences in the prevailing occupational structure.
Keywords: J16; J24; 330; occupational choice; occupational segregation; gender norms; preferences; intergenerational transmission; regional occupational structure